2020
DOI: 10.1158/1078-0432.ccr-19-0476
|View full text |Cite
|
Sign up to set email alerts
|

Adding Indoximod to Hypofractionated Radiotherapy with Anti-PD-1 Checkpoint Blockade Enhances Early NK and CD8+ T-Cell–Dependent Tumor Activity

Abstract: Purpose: There is growing interest in combinations of immunogenic radiotherapy (RT) and immune checkpoint blockade, but clinical responses are still limited. Therefore, we tested the triple therapy with an inhibitor of the indoleamine 2,3-dioxygenase pathway, which like immune checkpoints, downregulates the antitumor immune response.Experimental Design: Triple treatment with hypofractionated RT (hRT) þ anti-PD-1 antibody (aPD1) þ indoximod was compared with the respective mono-and dual therapies in two syngene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In preclinical mouse models, the local irradiation with a dose per fraction of 8-10 Gy delivered in two to three fractions has been shown to mimic a hypofractionated irradiation schedule in humans [24,33,34]. Recent research further supports the hypothesis that combined strategies are superior to induce efficient systemic anti-tumor responses [35,36].…”
Section: Hhp Vaccines Act Systemically But Only On Previously Irradiamentioning
confidence: 99%
“…In preclinical mouse models, the local irradiation with a dose per fraction of 8-10 Gy delivered in two to three fractions has been shown to mimic a hypofractionated irradiation schedule in humans [24,33,34]. Recent research further supports the hypothesis that combined strategies are superior to induce efficient systemic anti-tumor responses [35,36].…”
Section: Hhp Vaccines Act Systemically But Only On Previously Irradiamentioning
confidence: 99%
“…[32][33][34] Indoximod is commercially available and has shown promising immunomodulatory effects in canine metastatic melanoma and sarcoma when used in combination therapies. 35,36 Prior studies have demonstrated elevated numbers of CD4+ Foxp3+ regulatory T cells intratumorally and in the peripheral blood of dogs with gliomas, as well as an increased proportion of plasmacytoid dendritic cells. 29,37 In humans, the IDO pathway has been shown to play an important role in plasmacytoid dendritic cell-induced Foxp3+ regulatory T-cell differentiation.…”
Section: Figmentioning
confidence: 99%
“…A triple-combination therapy which inhibits PD-1 and MER proto-oncogene tyrosine kinase plus radiotherapy, increases NK cells infiltration in abscopal TME [ 264 ]. Adding indoximod, an inhibitor of IDO pathway, to radiotherapy and PD-1 blockade also enhances NK cell activity and shows great clinical response [ 265 ]. Another representative drug of triple-combination is selenium-containing nanoparticles,which delivers doxorubicin to the tumor site and releases high energy rays.…”
Section: Introductionmentioning
confidence: 99%